2018
DOI: 10.1039/c7sm02294h
|View full text |Cite
|
Sign up to set email alerts
|

Inertio-capillary cross-streamline drift of droplets in Poiseuille flow using dissipative particle dynamics simulations

Abstract: We find using dissipative particle dynamics (DPD) simulations that a deformable droplet sheared in a narrow microchannel migrates to steady-state position that depends upon the dimensionless particle capillary number , which controls the droplet deformability (with V the centerline velocity, μ the fluid viscosity, Γ the surface tension, R the droplet radius, and H the gap), the droplet (particle) Reynolds number , which controls inertia, where ρ is the fluid density, as well as on the viscosity ratio of the dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 37 publications
4
14
1
Order By: Relevance
“…Without polymer, the droplet initially migrated outward as f x increased, but the peak of this distribution moved inward with additional increases in f x (Fig. 7a), consistent with the simulations of Marson et al 35 At φ p = 5.0% (Fig. 7b), there was an initial trend to focus when f x 0.003 ε/d.…”
Section: B Droplet Distributionsupporting
confidence: 86%
See 4 more Smart Citations
“…Without polymer, the droplet initially migrated outward as f x increased, but the peak of this distribution moved inward with additional increases in f x (Fig. 7a), consistent with the simulations of Marson et al 35 At φ p = 5.0% (Fig. 7b), there was an initial trend to focus when f x 0.003 ε/d.…”
Section: B Droplet Distributionsupporting
confidence: 86%
“…In this article, we test and confirm this hypothesis using particle-based computer simulations of the crossstream migration of a Brownian fluid droplet in a polymer solution under Poiseuille flow. Although the droplet migrated outward in a Newtonian solvent (in agreement with prior simulations 35 ), we found that it focused onto the channel centerline in solutions of sufficiently long polymers at modest concentrations. The flow-rate dependence of the focusing was nontrivial due to a combination of effects from droplet deformation and the elastic force exerted by the polymers.…”
Section: Introductionsupporting
confidence: 89%
See 3 more Smart Citations